Therapeutic effect of gold nanoparticles on DSS-induced ulcerative colitis in mice with reference to interleukin-17 expression - Amira M. Abdelmegid (Nature Portfolio, 2019)
Abstract Ulcerative colitis (UC) is among the most challenging human diseases. Nanotechnology has incontestable promising outcomes in inflammatory bowel diseases. This study aimed to investigate the therapeutic effect of naked gold nanoparticles (AuNPs) on dextran sodium sulphate (DSS) induced ulcerative colitis in mice. We also examined the expression of interleukin-17 (IL-17) following AuNPs treatment. Mice were randomly divided into control, DSS and DSS+ AuNPs groups. Severity of colitis was assessed by disease activity index (DAI) measurement. At the end of the experiment, the final body weights were recorded. The colon was dissected and processed for histopathological examinations by light and electron microscopes. Colon homogenates were prepared for assay of tissue malondialdehyde (MDA) and real-time PCR analysis of IL-17A. Immunohistochemical localization of IL-17A was carried out. Scanning electron microscopy (SEM) and Energy Dispersive X-ray (EDX) detector were used to detect the presence of AuNPs in the colonic tissue of DSS+ AuNPs groups. Our results showed that AuNPs effectively targeted the colonic tissue, and reduced changes induced by DSS. The underlying mechanisms could be related to anti-oxidant effect (as evident by decreasing tissue MDA) and anti-inflammatory potential of AuNPs. Our study draws attention to as a novel therapeutic strategy for treating UC.